Serviço Social e terceiro setor: considerações sobre as atuais relações e condições de trabalho para o Assistente Social em Natal - Carneiro, Elizangela dos Santos (2005)
The present study analyses the actual relations and work conditions found in the third sector in Natal city, in the context of productive restoration and increasingly retraction from the State in providing Social Service before the new approach that has been destined to the social issue. The study talks about the work of the social worker when fighting the different expressions the social issue has, such as social service provision as a way of teamwork associated to work relations and conditions, to accessible resources and quality control management. These are elements that affect and interfere in the accomplishment and in the work of the social worker itself. The State s improvement, according to neoliberal-political precepts and increasingly retraction from the public investment in the areas of social concern (health, social welfare, assistance) and in the wage and employment policy, besides expanding the partnership with the public and private areas, in search for social services with quality, it has diversified the structures of the professional work with the growth of the so called third sector institutions. However, the absorption of the social workers by the third sector groups in general, has as major features the impoverishment of work relations, the maintenance of an unequal salary model, pointing out the deadline contracts and/or single tasks that generate work instability. The research debates, with a critical view and full perspective, over the conception of the third sector, interpreted as an action that expresses functions and values, treated as a real phenomenon generated from the restoration of the capital based on neoliberal principles. This study aims for responding what the established work relations are and under what work conditions the social worker has been fitting in the third sector and how such a reality echoes in the current work conditions for a social work in the city of Natal, before this new model of state intervention that transfers part of the social service provision to distinctive divisions of society, among them the so called third sector. The research results have shown that like the other workers the social worker passes through the same crises, dilemmas, advances and challenges that occur in the world of employment and which are expressed in the drop of salary average in the growth of contemporary contracts, unemployment, and in the ever more selective requirements to one be included in the social spaces, where the professional work is done, having as a result a greater impoverishment of work relations and conditions as well as more vulnerability as a salaried occupation